Conversion to enteric‐coated mycophenolate sodium from mycophenolate mofetil in stable renal transplant patients: Results of an Asia–Pacific study. Issue 1 (17th December 2012) - Lee, Po‐Huang; Vathsala, Anantharaman; Han, Duck Jong; Chan, Tak‐Mao; Wong, Hin‐Seng; Woodcock, Chad; Kurstjens, Nicol; ,; Sivaraman, Pary; Chu, Sheng‐Hsien; Hsieh, Hwei‐Ho; Hsu, Kuo‐Hsiung; et al.
Abstract : This study enrolled 112 patients from 16 Asian centres in Asian countries demonstrating that enteric‐coated mycophenolate sodium is a safe and effective alternative to mycophenolate mofetil. The incidence of gastrointestinal upset was reduced. Abstract: Aim: Mycophenolate mofetil has proven efficacy in the prophylaxis of acute rejection in solid organ transplantation; however, gastrointestinal intolerance can risk this efficacy because of associated dose adjustments and discontinued treatment. Enteric‐coated mycophenolate sodium has demonstrated improved gastrointestinal tolerability, but the data in Asian subjects are scarce. Methods: This was a Phase‐IIIb, open‐label, single‐arm, multicentre, prospective 6‐month study which investigated safety and graft function in stable maintenance renal transplant recipients of Asian origin, after switching from mycophenolate mofetil to enteric‐coated mycophenolate sodium at least 3 months after transplantation. Primary end‐points included renal allograft function and safety parameters. Results: The study recruited patients from 16 centres in Asian countries. The intention‐to‐treat and safety populations both included 122 patients. Graft function remained stable over the course of the study as measured by creatinine clearance and glomerular filtration rate. At 6 months the incidence of any gastrointestinal adverse events was 20.5% ( n  = 25), none of which required dose adjustments. There were only three cases of biopsy proven acute rejection with no reports of graft loss or death. Conclusion: This study demonstrated that enteric‐coated mycophenolate sodium is a safe and effective alternative to mycophenolate mofetil in Asian kidney transplant recipients.